Multi-parametric evaluation of electrical, biogas and natural gas geothermal source heat pumps. (January 2021) - Blázquez, Cristina Sáez; Borge-Diez, David; Nieto, Ignacio Martín; Martín, Arturo Farfán; González-Aguilera, Diego
Abstract: The use of low-impact energy sources is gradually growing with the aim of reducing greenhouse gases emission and air pollution. The alternatives offered by geothermal systems are one of the key solutions for a future renewable development, enabling the electrification of heating systems and the use of biofuels. This research addresses an overview of geothermal heating systems using ground source heat pumps in different European countries. Besides the traditional electrical heat pumps, gas engine heat pumps aided by natural gas or biogas are analysed in three areas. From a previous research, the technical parameters defining the geothermal system are used here to evaluate the most appropriate system in each scenario. The evaluation of different influential factors (operational costs, initial investment, environmental impact, and availability) allows defining the most recommendable systems for each area. Results of this multi-parametric study show that gas engine heat pumps aided by biogas could mean an excellent solution in all countries, also contributing to the management of waste and polluting substances. If biogas systems were not available, the electrical heat pump would be the first option for areas 1 and 3 (Italy and Sweden) but not for area 2 (United Kingdom), where natural gas is preferred. Graphical abstract: Image 1 Highlights: Electrical, biogas and natural gas geothermal heat pumps are evaluated. A multi-parametric analysis is performed on three different European scenarios. The evaluation of the energy mix is essential to select the geothermal heat pump in each location. Results are crucially influenced by the particular energy conditions of the country. Biogas heat pumps have a huge potential to be worldwide used for heating and cooling purposes.